ETNOGRAFI SEBAGAI ALAT UKUR IMPLEMENTASI KMA 183 TAHUN 2019 ‎DALAM PEMBELAJARAN AGAMA ISLAM DI MADRASAH - Sutarno Sutarno; Uky Fatanun Fiqih (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
Global changes that are so fast trigger various challenges, especially the world of education. Madrasah is an educational institution that emphasizes the religious aspect and does not escape the challenges of education. The implementation of KMA Number 183 in 2019 as a form of response to the implementation of the 2013 curriculum which has a